Development and Growth of Tariqat in Tasawuf in Indonesia - Syarifuddin (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
The aims of this study are to find out Development and Growth of Tariqat in Tasawuf in Indonesia. This study use qualitative research method. The result of this study shows that accesses that arise in practicing the teachings of Sufism are caused by misunderstandings, and therefore do not need to be used as a reason to reject it. The thriving life of kebatinan kebatinan schools and clinical teachings in Indonesia is the result of people's inclination to like Sufism, but they do not receive proper channels and guidance so that it often becomes an obstacle to smooth development. Therefore, Islamic Sufism is a teaching that is capable and appropriate to guide the misguided teachings of kebatinan and clinics in the right direction to be deployed in the field of development. The more the true teachings of Sufism are broadcast and practiced, the stronger people's belief in God Almighty will be.